2019
DOI: 10.21203/rs.2.12367/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-fat dietary consumption promotes disease progression in a surgical joint destabilisation murine model of osteoarthritis: role of systemic eicosanoids and circulating monocytes

Abstract: Background In this study we investigated the contribution of high-fat diet-induced metabolic overload to osteoarthritis (OA) progression originally caused by mild mechanical trauma to the mouse knee joint. We hypothesized that metabolic stress would induce a proinflammatory environment by altering systemic lipid levels and immune cell populations. Methods Twelve-week-old male C57BL/6J mice (n=20) were given a low-fat diet (LFD, 10%kcal from fat) or high-fat diet (HFD, 45%kcal from fat) for 18 weeks. OA was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…In patients with OA, it was found that intermediate monocytes are enriched in the synovial fluid compared to the circulation and that higher levels of intermediate monocytes correlate with worse KOOS and WOMAC function scores [ 123 ]. In mice fed a high-fat diet, increased monocyte activation was seen in addition to increased joint damage, with long-term feeding showing increased levels of systemic intermediate monocytes [ 124 ]. Increased intermediate monocyte levels could influence OA development via differentiation to pro-inflammatory macrophages in the synovium and IPFP, but also via differentiation to osteoclasts in the subchondral bone [ 125 ].…”
Section: Macrophages and The Metabolic Oa Phenotypementioning
confidence: 99%
“…In patients with OA, it was found that intermediate monocytes are enriched in the synovial fluid compared to the circulation and that higher levels of intermediate monocytes correlate with worse KOOS and WOMAC function scores [ 123 ]. In mice fed a high-fat diet, increased monocyte activation was seen in addition to increased joint damage, with long-term feeding showing increased levels of systemic intermediate monocytes [ 124 ]. Increased intermediate monocyte levels could influence OA development via differentiation to pro-inflammatory macrophages in the synovium and IPFP, but also via differentiation to osteoclasts in the subchondral bone [ 125 ].…”
Section: Macrophages and The Metabolic Oa Phenotypementioning
confidence: 99%